Hope and struggle in the policed city: black criminalization and resistance in Philadelphia - Dirkson, Menika B. (New York University Press, 2024)
"Hope and Struggle in the Policed City: Black Criminalization and Resistance in Philadelphia explores how local concerns about poverty-induced, black crime cultivated by police, journalists, and city officials sparked a rise in tough on crime policing while community activists resisted with social welfare programs in Philadelphia"--